2017
DOI: 10.1200/jco.2017.74.6065
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic Therapy for Stage IV Non–Small-Cell Lung Cancer: American Society of Clinical Oncology Clinical Practice Guideline Update

Abstract: Purpose Provide evidence-based recommendations updating the 2015 ASCO guideline on systemic therapy for patients with stage IV non-small-cell lung cancer (NSCLC). Methods The ASCO NSCLC Expert Panel made recommendations based on a systematic review of randomized controlled trials from February 2014 to December 2016 plus the Cancer Care Ontario Program in Evidence-Based Care's update of a previous ASCO search. Results This guideline update reflects changes in evidence since the previous guideline update. Fourte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
326
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 509 publications
(336 citation statements)
references
References 29 publications
7
326
0
3
Order By: Relevance
“…Osimertinib is a third-generation, EGFR-TKI that potently and selectively inhibits both EGFR sensitizing and EGFR T790M resistance mutations [5,17,18]. Based on positive results from the AURA trial program and FLAURA first-line study, osimertinib is recommended in the US as a first-line treatment option for patients with EGFR mutation-positive advanced NSCLC and as a second-line treatment for patients with T790M-positive NSCLC following disease progression on a first-line EGFR-TKI therapy (erlotinib, gefitinib, or afatinib) [12,19]. Thus, EGFR mutation testing at diagnosis and T790M testing following progression on an EGFR-TKI are now recommended in clinical guidelines and are standard of care in clinical practice [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osimertinib is a third-generation, EGFR-TKI that potently and selectively inhibits both EGFR sensitizing and EGFR T790M resistance mutations [5,17,18]. Based on positive results from the AURA trial program and FLAURA first-line study, osimertinib is recommended in the US as a first-line treatment option for patients with EGFR mutation-positive advanced NSCLC and as a second-line treatment for patients with T790M-positive NSCLC following disease progression on a first-line EGFR-TKI therapy (erlotinib, gefitinib, or afatinib) [12,19]. Thus, EGFR mutation testing at diagnosis and T790M testing following progression on an EGFR-TKI are now recommended in clinical guidelines and are standard of care in clinical practice [3].…”
Section: Discussionmentioning
confidence: 99%
“…When considering the use of targeted therapies for anaplastic lymphoma kinase (ALK)-rearranged and epidermal growth factor receptor (EGFR) mutation-positive NSCLC, tumor biopsy or blood-based testing is required to confirm tumor mutation status and assist with appropriate patient selection [3,12,13]. With the increase in availability of additional mutation-and translocation-based targeted therapies and immunotherapies, molecular and immune micro-environment testing at diagnosis and progression have become increasingly important to understand molecular mechanisms of resistance and for the effective management of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…These agents have produced durable clinical responses and antitumor activity in Phase I trials, leading to subsequent randomized Phase II and III trials that demonstrated significant improvements in overall survival when compared with cytotoxic chemotherapy alone [12][13][14][15][16]. These studies have established PD-1/PD-L1 pathway blockade as a powerful new line of therapy for patients with advanced NSCLC following progression after platinum-based therapy [9,11]. Despite unprecedented improvements in clinical outcomes, less than 20% of patients respond to anti-PD-1/PD-L1 agents, necessitating strategies that explore combined treatment modalities in order to extend the benefits of immune checkpoint blockade to a broader patient population.…”
mentioning
confidence: 99%
“…Immune checkpoint inhibitors of the PD-1/PD-L1 pathway have emerged as a promising new therapeutic strategy [8][9][10][11]. These agents have produced durable clinical responses and antitumor activity in Phase I trials, leading to subsequent randomized Phase II and III trials that demonstrated significant improvements in overall survival when compared with cytotoxic chemotherapy alone [12][13][14][15][16].…”
mentioning
confidence: 99%
See 1 more Smart Citation